DEVELOPMENT AND VALIDATION OF A RP - HPLC METHOD FOR DETERMINATION OF ETORICOXIB IN PHARMACEUTICAL DOSAGE FORMS - SACHIN GHOLVE; OMPRAKASH BHUSNURE; OOMMEN MATHEW; JAIPRAKASH SANGSHETTI (International Journal of Pharma and Bio Sciences, 2016)
To develop a simple, cheap, accurate, precise, linear and rapid Reverse Phase High Performance Liquid Chromatographic (RP-HPLC) method and validate as per ICH & USP guidelines for the quantitative estimation of Etoricoxib in pharmaceutical dosage forms. The separation was conducted by using mobile phase consisting of methanol: ammonium acetate buffer:acetonitrile in the ratio (70:20:10). The wavelength was found at 235nm. Chromatographic determination was performed on Agilent 1220 Infinity LC with ezchrome software with variable wavelength detector. The separation was conducted by using Zebra Eclipse XDB-C-18 (4.6×150×5µm) at the flow rate of 1.0 ml/min using variable wavelength detector. The developed method resulted in etoricoxib eluting at 2.083 min. The method was found to be linear over the concentration range 2-12µg/ml with coefficient regression R2-0.9988. The precision is exemplified by relative standard deviation of 1.15 to 1.8 %. Percentage Mean recovery was found to be in the range of 97to99%, during accuracy studies. The limit of detection (LOD) and limit of quantitiation (LOQ) was found to be 5 ng/ml and 15 ng/ml respectively. A cheap, accurate, precise, linear and rapid RP-HPLC method was developed and validated for the quantitative estimation of etoricoxib tablets as per ICH guidelines and hence it can be used for the routine analysis in various pharmaceutical industries.